1989
DOI: 10.1161/01.hyp.13.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Renin regulation in type II diabetes mellitus: influence of dietary sodium.

Abstract: Numerous abnormalities in the renin-angiotensin system have been described in diabetes mellitus. Plasma renin activity (PRA) has been noted to be low, normal, and high La diabetic patients; these variable results may be explained by differences in patient selection and standardization of study conditions. We evaluated PRA and inactive renin responses in Type II normotensive (n=7) and hypertensive (n=12) diabetic patients specifically selected for no or minimal evidence (background retinopathy) for microvascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Previous studies suggest that a positive relationship between T2DM and salt sensitivity exists, and this relationship is driven by low PRA levels and an increased frequency of LR status (5)(6)(7)30). Our carefully controlled human study refutes these observations.…”
Section: Figsupporting
confidence: 83%
“…Previous studies suggest that a positive relationship between T2DM and salt sensitivity exists, and this relationship is driven by low PRA levels and an increased frequency of LR status (5)(6)(7)30). Our carefully controlled human study refutes these observations.…”
Section: Figsupporting
confidence: 83%
“…It is by indirect approaches that we have studied renal hemodynamics in several groups, including blacks. We studied renal perfusion and function in 32 healthy blacks and 82 age-matched healthy whites on a high-salt diet [26]. Although the glomerular filtration rate was similar, RPF was significantly less in age-matched blacks (568 ± 18) than whites (620 ± 13 mL/min/1.73 m 2 ; P = 0.0063) (Fig.…”
Section: Is Low Renin In Blacks Paradoxical?mentioning
confidence: 97%
“…As PRA was identical in these healthy whites and blacks, the findings suggest that it is the intrarenal-renin system that is activated in blacks. Intrarenal activation of angiotensin II would operate via the short feedback loop to suppress systemic levels of renin, a paradoxic response [26]. If the kidneys of blacks were activated with angiotensin II, this would cause more vasoconstriction with resultant increased susceptibility to injury, especially when diseases like hypertension are superimposed.…”
Section: Is Low Renin In Blacks Paradoxical?mentioning
confidence: 99%
“…25 Another controversial issue is whether or not patients with type 2 diabetes have a poorly suppressible renin release in response to a high salt diet. 26 When comparing renin-angiotensin-aldosterone system (RAAS) in hypertensive patients suffering from a non-late stage type 2 diabetes and essential hypertensives without diabetes, a higher incidence of low renin state was found in patients with essential hypertension. 21 Those authors observed an identical incidence of non-modulators in patients with essential hypertension or type 2 diabetes after exclusion of the low renin patients.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%